Analysis of Students' Mathematical Problem Solving Skills on Opportunity Material - Gaitsa Zahira Shofa; Ari Septian; Rani Sugiarni (PRISMA, 2026)
Problem-solving abilities are an important ability in understanding and applying mathematical concepts, including probability material that requires analysis and logical reasoning. This study aims to describe the mathematical problem-solving abilities of vocational high school students on probability material and to identify the difficulties faced by students in solving related problems. This research uses a descriptive qualitative method with a subject group of 27 students from class XI Yankes 3 at Vocational School Bunga Persada Cianjur for the 2024/2025 academic year who have studied probability material. Data collection techniques were carried out through mathematical problem-solving tests, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The research results show that students' mathematical problem-solving ability in probability material is still classified as low. Based on the test results, only 3.7% of students are in the high category, 14.8% in the medium category, and 81.5% in the low category. If reviewed based on its stages, the percentage of student achievement is as follows: understanding the problem at 32,2%, planning the solution at 67,1%, executing the solution at 63,9%, and reviewing at 5,6%.The reviewing stage has the lowest achievement. Students' difficulties primarily lie in understanding problems related to probability material, constructing mathematical models to determine formulas for finding event probabilities, and checking the final results of probabilities found in story problems. These findings highlight the importance of reinforcing the understanding of basic concepts and contextual problem-solving exercises in probability learning to enhance the mathematical problem-solving abilities of vocational high school students.